Inheritance Property Distribution Models Among the Muslim Community of Borneo-Nusantara - Muhammad Hasan; Dahlia Haliah Ma'u; Mualimin Mochammad Sahid (Faculty of Syariah, State Islamic University of Raden Intan Lampung, 2024)
Indexed by Scopus